A 'wiring diagram' for source strength traits impacting wheat yield potential. (5th November 2022) - Murchie, Erik H; Reynolds, Matthew; Slafer, Gustavo A; Foulkes, M John; Acevedo-Siaca, Liana; McAusland, Lorna; Sharwood, Robert; Griffiths, Simon; Flavell, Richard B; Gwyn, Jeff; Sawkins, Mark; Carmo-Silva, Elizabete
Abstract: Source traits are currently of great interest for the enhancement of yield potential; for example, much effort is being expended to find ways of modifying photosynthesis. However, photosynthesis is but one component of crop regulation, so sink activities and the coordination of diverse processes throughout the crop must be considered in an integrated, systems approach. A set of 'wiring diagrams' has been devised as a visual tool to integrate the interactions of component processes at different stages of wheat development. They enable the roles of chloroplast, leaf, and whole-canopy processes to be seen in the context of sink development and crop growth as a whole. In this review, we dissect source traits both anatomically (foliar and non-foliar) and temporally (pre- and post-anthesis), and consider the evidence for their regulation at local and whole-plant/crop levels. We consider how the formation of a canopy creates challenges (self-occlusion) and opportunities (dynamic photosynthesis) for components of photosynthesis. Lastly, we discuss the regulation of source activity by feedback regulation. The review is written in the framework of the wiring diagrams which, as integrated descriptors of traits underpinning grain yield, are designed to provide a potential workspace for breeders and other crop scientists that, along with high-throughput and precision phenotyping data, genetics, and bioinformatics, will help build future dynamic models of trait and gene interactions to achieve yield gains in wheat and other field crops. Abstract : We summarize and update the origins of and limitations to sources of photosynthate in the context of a 'wiring diagram', depicting source and sink within wheat growth and development.